Peningkatan keterampilan basic photography dengan smartphone dan penyusunan laporan keuangan UMKM - Zubaidi Indra; Yenni Agustina; Kiagus Andi (Yumary: Jurnal Pengabdian kepada Masyarakat, 2021)
Technology and financial reports have a vital role in business life. Technology can help MSME players in marketing their products to areas that are difficult to reach for them. One form of technology that has an important role is cell phones. This tool, which is better known as a communication tool, can also act as an attractive image-producing tool that can support MSME players in marketing their products. However, not all MSMEs can use this tool optimally due to the lack of knowledge and skills in photography. Meanwhile, financial reports for stakeholders are no less critical for the continuity of MSME businesses, especially in obtaining financial assistance from the government. Kelurahan Tanjung Raya, especially RT 015, is out of the population working as a business actor. However, the development of MSMEs was not so fast due to their lack of knowledge in marketing goods and preparing financial reports. Based on this phenomenon, the team conducted a Community Service attended by 10 MSME actors. This service activity was carried out at the Bunda Delima Akper for 1 day, considering it was in a covid 19 situation. At the time of this activity, the participants were so enthusiastic about taking part in training and practicing photography so that this activity could provide positive values for the participants.